2014
DOI: 10.1186/1756-9966-33-8
|View full text |Cite
|
Sign up to set email alerts
|

The activation of c-Jun NH2-terminal kinase is required for dihydroartemisinin-induced autophagy in pancreatic cancer cells

Abstract: Backgroundc-Jun NH2-terminal kinases (JNKs) are strongly activated by a stressful cellular environment, such as chemotherapy and oxidative stress. Autophagy is a protein-degradation system in which double-membrane vacuoles called autophagosomes are formed. The autophagy-related gene Beclin 1 plays a key role in this process. We previously found that autophagy was induced by dihydroartemisinin (DHA) in pancreatic cancer cells. However, little is known about the complex relationship between ROS, JNK activation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 48 publications
0
54
0
Order By: Relevance
“…In the ovarian cancer cells, autophagy was also activated by DHA via the mTOR pathway, although the association between apoptosis and autophagy was not proven30. JNK-mediated Beclin 1 expression was demonstrated to be involved in the DHA-induced autophagic activation in human pancreatic cancer cell lines31. Autophagy controlling cellular homeostasis has been found to inhibit catabolism and inflammation in cells under stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the ovarian cancer cells, autophagy was also activated by DHA via the mTOR pathway, although the association between apoptosis and autophagy was not proven30. JNK-mediated Beclin 1 expression was demonstrated to be involved in the DHA-induced autophagic activation in human pancreatic cancer cell lines31. Autophagy controlling cellular homeostasis has been found to inhibit catabolism and inflammation in cells under stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, JNK/SAPK activation is considered an important apoptosis-inducing factor that exerts proapoptotic effects on apoptosis of cancer cells (36,37). Previous studies have indicated that JNK/SAPK activation results in an increase in the number of apoptotic cells in response to several anticancer agents in pancreatic cancer (38,39). The present study demonstrated that treatment with moscatilin induced sustained activation of JNK/SAPK, and the phosphorylation of JNK/SAPK was dependent on ROS generation, which was prevented by treatment with the ROS scavenger NAC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Seki et al (42) highlighted the relevant role of JNK signaling in the initiation and progression of liver cancer, and Leventaki et al (43) reported that JNK activation induces tumor cell proliferation in classical Hodgkin lymphoma. Jia et al (44) reported that the activation of JNK contributes to dihydroartemisinin-induced autophagy in pancreatic cancer cells, and Shi et al (45) suggested that JNK enhances the tumor suppressive role of p53 and promotes apoptosis in several cell cancer lines, including colon, breast carcinoma and osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%